The Process of "Pushing Out": Accumulated Disadvantage across School Punishment and Math Achievement Trajectories. Issue 6 (September 2022) - Jabbari, Jason; Johnson, Odis
Students drop out of school for a variety of reasons, yet are "pushed out" when they exhibit traits that are deemed undesirable to school officials, such as misbehavior and academic failure. While much of the previous research on pushouts views the phenomenon as a discrete occurrence often attributed to either misbehavior or academic failure, we recognize the underlying relationships between punishment and achievement, and therefore conceptualize pushing out as a process of both disciplinary involvement and academic exclusion over time. Using structural equation modeling (SEM) with a nationally representative longitudinal study of high school students (HSLS-09), we find that significant relationships among punishment and math achievement (including math attitudes, ability, and course-taking) have the effect of pushing students out of high school over time. We note the importance of race and ethnicity within these relationships and close with a discussion of policy implications.